Caprine arthritis encephalitis and caseous lymphadenitis in goats: use of bulk tank milk ELISAs for herd‐level surveillance. (14th February 2015) - Nagel‐Alne, G. E.; Valle, P. S.; Krontveit, R.; Sølverød, L. S.
Abstract : The objective of this study was to evaluate the diagnostic performance of two ELISA tests applied to bulk tank milk (BTM) as the first part of a two‐step test scheme for the surveillance of caprine arthritis encephalitis (CAE) and caseous lymphadenitis (CLA) infections in goats. The herd‐level BTM tests were assessed by comparing them to the test results of individual serological samples. The potential for refining the cut‐off levels for BTM tests used as surveillance tools in a population recently cleared of infection was also investigated. Data was gathered on serum (nCAE =9702 and nCLA =13426) and corresponding BTM (nCAE =78 and nCLA =123) samples from dairy goat herds enrolled in the Norwegian disease control and eradication programme 'Healthier Goats'. The results showed that the sensitivity and specificity of the CAE ELISA BTM test with respect to detecting ≥2 per cent within‐herd prevalence were 72.7 per cent and 86.6 per cent, respectively. For the CLA ELISA BTM the sensitivity and specificity were 41.4 per cent and 81.7 per cent, respectively, for the same goal of detection. The results suggest that BTM testing can be applied as a cost‐effective first step for early detection of CAE and CLA infection.